FRI0347 Predictive factors of long-term clinical outcome in patients with ocular involvement secondary to behcet's disease. (23rd January 2014) - Ferrari, C.; Talarico, R.; Stagnaro, C.; d'Ascanio, A.; Tani, C.; Baldini, C.; Bazzichi, L.; Mosca, M.; Bombardieri, S.
Abstract : Background: Behçet's disease (BD) is a multisystemic, chronic relapsing inflammatory disease classified among the vasculitis. Eye involvement represent one of the most serious manifestation of BD and occurs in half of all patients. It seems more frequent and severe among young males and, unluckily, it still represents a significant cause of morbidity. Objectives: The aims of the study was to identify factors able to predict long-term outcome in patients with BD Methods: Forty-seven patients (29 males and 18 females; mean age at the onset 29±5 years) with a diagnosis of BD according the ISG criteria were studied. The probability of clinical relapse after remission of the first ocular attack was calculated using the Kaplan-Meier method. Predictors of long-term outcome were identified by univariate analysis using the log-rank test and by multivariate analysis using Cox proportional hazards regression models. Results: The mean time between the first initial symptoms of BD and the onset of eye lesions was 3±2 years. The number of ocular attacks were the following: 32 posterior uveitis, 27 anterior uveitis, 21 retinal vasculitis, while panuveitis developed in 17 subjects. Medical treatments received at time of the study were: cyclosporine A (n=21), infliximab (n=13, azathioprine (11), adalimumab (2). The cumulative relapse rates at 1 year, 3 years, and 5 years after remission of the first ocular attack were 20%, 38.7%, and 42%, respectively. On multivariate analysis, a younger age (<30 years) at the onset of ocular involvement, male sex and medical treatments other than biological agents represent independent predictive factors for relapse in BD patients with ocular involvement. Conclusions: As awaited, the use of anti TNF alpha agents seems to be associated with a positive effect on maintaining remission in ocular involvement due to BD. However, as literature data suggest, younger age and male sex represent predictive factors of poor long-term clinical outcome. Disclosure of Interest : None Declared